2020
DOI: 10.1007/s42322-020-00072-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of music making outdoors on primary school aged pupils (aged 7–10 years) in the soundscape of nature from the perspective of their primary school teachers

Abstract: The benefits of taking pupils’ learning outdoors have been widely reported around the world. However, it is argued the simple act of stepping outside the classroom does not inevitably bring rewards. This study examines teachers’ perceptions of the impact of primary school pupils’ music-making in various outdoor rural locations. It analyses qualitative data from semi-structured interviews with seven teachers from six different primary school classes, who observed their classes as they took part in the music-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Eleven reports of studies were included in this systematic review ( Bruni et al, 2017 ; Gray and Birrell, 2015 ; Gray and Thomson, 2016 ; Adams and Beauchamp, 2018 , 2019 , 2020 ; Murphy, 2018 ; Arbuthnott and Sutter, 2019 ; Sobko et al, 2020 ; Tiplady and Menter, 2021 ; Moula et al, 2021 ). However, two studies were reported in more than one article ( Gray and Birrell, 2015 ; Gray and Thomson, 2016 ; Adams and Beauchamp, 2018 , 2019 , 2020 ). Therefore, the findings from eight studies were synthesized.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven reports of studies were included in this systematic review ( Bruni et al, 2017 ; Gray and Birrell, 2015 ; Gray and Thomson, 2016 ; Adams and Beauchamp, 2018 , 2019 , 2020 ; Murphy, 2018 ; Arbuthnott and Sutter, 2019 ; Sobko et al, 2020 ; Tiplady and Menter, 2021 ; Moula et al, 2021 ). However, two studies were reported in more than one article ( Gray and Birrell, 2015 ; Gray and Thomson, 2016 ; Adams and Beauchamp, 2018 , 2019 , 2020 ). Therefore, the findings from eight studies were synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review encompasses data from 602 participants in total, with sample sizes ranging from 11 to 187 participants. Where more than one study had utilized data collected from the same samples ( Gray and Birrell, 2015 ; Gray and Thomson, 2016 ; Adams and Beauchamp, 2018 , 2019 , 2020 ), the participants numbers have been included only once in the systematic review’s total.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations